Karakteristik Radio Cinta Ayu Senada (CAS) FM - Winda Kustiawan; Niatul Mukarramah; Razkiatul Fitri Matondang; Silvi Hibriyanti; Suci Nabila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Referring to its understanding in The Encyclopedia of Americana International, radio is a communication tool that uses electromagnetic waves that propagate through space at the speed of light. Electromagnetic waves used in radio communications are similar to light and heat waves, but have a lower frequency. This study used descriptive qualitative method. The type of data used is secondary data. Secondary data obtained from books, theses, journals, articles and the internet. This study aims to analyze the characteristics of CAS FM radio. The characteristics of radio include sound, transmission, contain interference, create listeners' imaginations, and are synonymous with music. The data collection technique used by the researcher was to conduct interviews with sources who played an important role and understood the characteristics of CAS FM radio.